Reform of the criminal law in Poland - Byczyk, Marcin (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The author discusses the main ideas behind the proposed reform of the criminal law in light of the project conveyed to the Polish Sejm on the 15th of May 2014. The proposed changes, being the most significant ones since the recodification of the criminal law in 1997, are based on the correct presumption that the deficiencies in current Polish criminal policy lead to overly repressive criminal law. A detailed analysis of the project, however, shows that it is not free from failures, in terms of both the formulation of legal norms as well as the reforms to institutions of the criminal law with respect to the application of penalties. It also does not take into account the arguments formulated in recent years regarding the reform of the criminal law. This leads to the conclusion thatthe proposed changes, though rightly focused on improving the most fundamental tools of criminal policy, nonetheless have the character of an ad hoc reform, which even had some elements of penal populism, influencing in such a negative way the shape of the criminal law in recent years. Yet most of those controversial changes have been abandoned during the parliamentary works on this since 1.07.2015 binding law.